2015
DOI: 10.3390/md13063276
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Tumor Suppressor PP2A Emerges as a Potential Therapeutic Strategy for Treating Prostate Cancer

Abstract: Protein phosphatase 2A (PP2A) is a tumor suppressor complex that has recently been reported as a novel and highly relevant molecular target in prostate cancer (PCa). However, its potential therapeutic value remains to be fully clarified. We treated PC-3 and LNCaP cell lines with the PP2A activators forskolin and FTY720 alone or combined with the PP2A inhibitor okadaic acid. We examined PP2A activity, cell growth, prostasphere formation, levels of PP2A phosphorylation, CIP2A and SET expression, and AKT and ERK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
4
24
0
1
Order By: Relevance
“…46 Specific PP2A subunit acts as a tumor suppressor and dysregulation of PP2A is common in human cancers. 25,47,48 Consistent with prior research, we revealed a suppression of PP2A-attributable phosphatase activity and corresponding increase in p-H3S10 in AFB 1 -induced cells, supporting a notion that persistent p-H3S10 conferred cells with an oncogenic activity. Given the results that PP2Ac is in complex with p-H3S10, we conclude that PP2A is involved in dephosphorylation of p-H3S10.…”
Section: Discussionsupporting
confidence: 91%
“…46 Specific PP2A subunit acts as a tumor suppressor and dysregulation of PP2A is common in human cancers. 25,47,48 Consistent with prior research, we revealed a suppression of PP2A-attributable phosphatase activity and corresponding increase in p-H3S10 in AFB 1 -induced cells, supporting a notion that persistent p-H3S10 conferred cells with an oncogenic activity. Given the results that PP2Ac is in complex with p-H3S10, we conclude that PP2A is involved in dephosphorylation of p-H3S10.…”
Section: Discussionsupporting
confidence: 91%
“…CIP2A was identified as a molecular target of FTY720, confirming previous observations in colorectal cancer that FTY720-induced CIP2A downregulation plays a key role in the antitumor activity of this drug [10]. Another study has reported an enhanced sensitivity to cabazitaxel in those prostate tumors that have progressed to castration resistance via loss of RB, which is a well-known target of PP2A activity that negatively regulates cell cycle progression in its active hypophosphorylated status [5].…”
mentioning
confidence: 62%
“…These observations together with the novel findings by Huang and co-workers could have important clinical implications defining a subgroup of prostate cancer patients who are candidates to benefit from the treatment with PP2A activators. However, an unanswered aspect from this study is the fact that it only analyzes CIP2A, and several other contributing mechanisms to PP2A inhibition have been described in prostate cancer such as alterations affecting PP2A subunits [11][12][13] or deregulation of the endogenous PP2A inhibitor SET [10,14]. Therefore, it remains necessary to evaluate the potential role of these alterations modulating cabazitaxel in prostate cancer via PP2A inactivation.…”
mentioning
confidence: 97%
“…The most well‐studied PP2A activator is FTY720 (fingolimod), which is a sphingosine‐1 receptor agonist. In vitro studies on prostate cancer have shown the tumor inhibitory effect of FTY720 . Additionally, FTY720 improves the survival in animal models of leukemia with little toxicity, indicating that activating PP2A might be a useful and safe strategy in cancer treatment …”
Section: Pps As Cancer Therapeutic Targetsmentioning
confidence: 99%